Sharia Compliance in the Practice of Buying and Selling Transactions (Al-Bay') in MSMEs: A Qualitative Study in Lamongan Regency - Nur Maulidah Apriliah Mahmudah Fauziah; Ahmad Munir Hamid; Huril A'ini (Danadyaksa: Post Modern Economy Journal, 2026)
One of the objectives of this study is to find out the extent to which owners and managers of MSMEs in Lamongan Regency apply Sharia law in buying and selling activities (al-bay'). This study uses a qualitative descriptive methodology. Eight micro, small, and medium enterprises (MSMEs) managers from various industry sectors were interviewed through in-depth interviews, observations, and documentation. Data reduction, data presentation, and conclusion drawing are all part of the interactive model used for data analysis. The survey results show that buying and selling activities carried out by small and medium business managers (SMEs) mostly comply with sharia values, including honesty, fairness, transparency, and avoiding gharar and usury. Everything has been established and agreed upon from the beginning, including a pricing system that is based on reasonable costs and profits. However, MSME actors' understanding of the concept of sharia is still practical and not theoretically comprehensive. Factors that affect sharia compliance include the level of understanding, business experience, religiosity, social environment, as well as external factors such as market conditions and consumer behavior. Thus, efforts are needed to increase sharia economic literacy through education and continuous assistance so that the implementation of sharia compliance can be carried out more optimally and consistently in daily business practices.